2012
DOI: 10.1097/prs.0b013e3182589dd5
|View full text |Cite
|
Sign up to set email alerts
|

The Auriculotemporal Nerve in Etiology of Migraine Headaches

Abstract: Findings from this cadaver study provide information relevant to the operative localization of potential compression points along the auriculotemporal nerve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
59
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 11 publications
0
59
0
2
Order By: Relevance
“…Since the inception of migraine surgery, the impact of other nerve branches such as the auriculotemporal, third occipital, and lesser occipital has come to play a significant role. 17,18,22,[28][29][30] These anatomical overlaps and irritation of the smaller peripheral branches may cloud the ability to adequately locate the correct site or nerve for decompression. More recently, the senior author has found that a handheld Doppler probe will almost invariably locate an arterial signal near a residual or new pain site, indicating a close association with vascular irritation.…”
Section: Discussionmentioning
confidence: 99%
“…Since the inception of migraine surgery, the impact of other nerve branches such as the auriculotemporal, third occipital, and lesser occipital has come to play a significant role. 17,18,22,[28][29][30] These anatomical overlaps and irritation of the smaller peripheral branches may cloud the ability to adequately locate the correct site or nerve for decompression. More recently, the senior author has found that a handheld Doppler probe will almost invariably locate an arterial signal near a residual or new pain site, indicating a close association with vascular irritation.…”
Section: Discussionmentioning
confidence: 99%
“…The ATN (V 3 ) wraps around the medial posterior aspect of the neck of the mandibular condyles to ascend in the preauricular region into the temporal region. Compression points have been identified in preauricular fascial bands as well as with the tortuous relationship between the superficial temporal artery and ATN [34].…”
Section: Anatomic Basis For Trigger Site Decompressionmentioning
confidence: 99%
“…7 Three distinct compression points have been identified. The first two relate to preauricular fascial bands described in relation to the external auditory meatus.…”
Section: Ideas and Innovationsmentioning
confidence: 99%
“…Three nerve-artery relation patterns have been described, including a single site of the artery crossing the nerve, a helical intertwining, and the nerve crossing over the artery. 7,8 The superficial temporal artery runs close enough to the skin surface to allow its signal to be readily detected with an ultrasound Doppler signal. Therefore, combining patient participation in identifying the temporal trigger site with the use of ultrasound Doppler provides the surgeon with a precise target for decompression.…”
Section: Ideas and Innovationsmentioning
confidence: 99%
See 1 more Smart Citation